Metabolic tumor burden: A new promising way to reach precise personalized therapy in PDAC. Issue 2 (10th April 2015) - Xiang, Jinfeng; Liu, Liang; Wang, Wenquan; Xu, Huaxiang; Wu, Chuntao; Xu, Jin; Liu, Chen; Long, Jiang; Ni, Quanxing; Yu, Xianjun
Highlights The treatment for pancreatic ductal adenocarcinoma (PDAC) is still in an austere predicament. People concentrate on screening effective factors to instruct a precise treatment. The conventional methods are always based on CT or serum tumor marker levels, which have limited merits. The authors introduce a new perspective for the pretreatment evaluation of PDAC based on cancer metabolism. Metabolic tumor burden may potentially serve as a new promising approach to reach precise personalized therapy in PDAC.